MOTIVASI BERPRESTASI PESERTA DIDIK DALAM PEMBELAJARAN DARING PADA MASA COVID-19 DI SMK NEGERI 7 PONTIANAK - Mila Ardila; M. Asrori; Yuline Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to explain an analysis of student achievement motivations in dalam jaringan learning during Covid-19 at Class X Vocational High School 7 Pontianak. This type of survey uses survey surveys. The sample for this study consisted of class X students and a total of 66 students. Sampling was done randomly. The survey method used is descriptive and quantitative. Data retrieval through indirect communication methods using closed surveys distributed via Google Forms links. Data analysis with percentage correction. As a result, the analysis of student achievement motivation in dalam jaringan learning during Covid-19 period has a high category, that is, the characteristics of achievement motivation in dalam jaringan learning during Covid-19 period, which is 96.87% of the category. It has been shown. good . The internal aspects of achievement motivation in dalam jaringan learning during Covid-19 were in the high category with a 96.56% share, and the external aspects of achievement motivation in dalam jaringan learning during Covid-19 were high with a 95.02% share. Category. Based on the above explanation, in general, an analysis of student achievement motivations in dalam jaringan learning during Covid-19 was successfully conducted in Class X students of Pontianak State 7 Vocational High School in 2022.